Assessing the implications of temperature extremes during the period 1959-2014 on the Inner Mongolia Plateau to sustainable development - Li, Chunlan; Du, Debin; Leal Filho, Walter; Wang, Jun; Bao, Gang; Ye, Mingwu; Ayal, Desalegn Yayeh; Shan, Yin; Bao, Yuhai; Hu, Richa (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
The study sought to foster a better understanding of the nature of extreme temperature events and variations, and their implications to sustainable development, based on 16 indices of extreme temperature obtained from 43 meteorological stations on the Inner Mongolia Plateau (IMP). By using linear trend and Mann-Kendall abrupt change tests to investigate temporal variation trends, coupled with spatial distribution patterns and abrupt changes of extreme temperature events, the study revealed that the IMP has experienced extreme warming during 1959–2014 with warm extremes increasing significantly (p < 0.01) and cold extremes apparently decreasing (p < 0.01). The most significant increasing trends of warm extreme indices occurred in the desert steppe area (DSA) and sand desert area (SDA), suggesting that warming trends for night-time indices were larger than for daytime indices, while the most significant decreases in cold extreme indices were detected in forest area (FA) and forest steppe area (FSA). In addition, the significant cold day and cold night indices showed a decreasing trend, while warm day and warm night indices showed an increasing trend across the entire study area. Moreover, the study identified that topography has a large impact on the spatial distribution of extreme temperature indices, as does the type of grassland, and the ubiquity of the heat island effect in constructed urban regions. Finally, the study posits that to mitigate the effects of extreme temperatures, it is imperative to foster adaptive actions based on the principles of sustainable development.